Carok :: Institusionalisasi kekerasan dalam masyarakat Madura - WIYATA, A. Latief (Universitas Gadjah Mada, 2001)
This carok research is the first study conducted in the form of a Doctoral dissertation. Previous studies were mainly in the forms of observations, researches sponsored by funding institutions and short essays accomplished by undergraduate students. That is why, so far, carok has not been understood properly and this causes many misleading assumptions about it. The main goals of this research are, therefore, to comprehend the meaning of carok. By using Western part of Madura as a place of study, this study gathers data through a life history approach to six carok cases taking place in 1994 and before. The fieldwork had been carried out for about ten months since August 1995. Because violence (including carok) locates in a social and cultural context of a society, it has to be elaborated consistently in regard to social and cultural conditions of Madurese, and it is particularly through analysis, thick descriptions, and interpretative studies, the meanings of carok in Madurese social and cultural atmosphere can be uncovered. The main finding of this research proves that carok does not follow a common non-Madurese perception that carok is all forms of vio/ence affixed to Madurese. It is, as a matter of fact, an institutionalisation of violence that has relations with cultural structure, social structure, social and economic conditions, religion, and education.